Assessment of non timber forest products in Baghmara Buffer Zone Community Forest, Chitwan, Nepal - Danekhu, Udisha; Shrestha, Rajeswar; Maharjan, Sanu Raja (Journal of Natural History Museum, 2018)
Non-Timber Forest Products (NTFPs) are the forest products except timber used for various purposes from which economic status of the country can be increased through green growth based economy. The study was conducted in Baghmara Buffer Zone Community Forest for the inventory, to document various uses and find out the preferred NTFPs potential for economic development of Community Forest User Groups. Stratified random sampling was applied in which 50 quadrats of size 25m×20m for trees, 100 subplots of 10m×10m for shrubs and 200 small subplots of 1m×1msize for herbs and climbers were taken. Parameters like density, frequency, abundance, importance value index, diversity index, evenness index and dominance index were calculated to find out the ecological status of NTFPs. Questionnaire survey of 100 households was done for studying different uses and interview with 10 key informants were carried out to identify 10 most preferred NTFPs. Altogether, 109 NTFPs were enumerated. Trewia nudiflora, Clerodendrum viscosum, Imperatacylindrica and Mikania micrantha were dominant tree, shrub, and herb and climber species accordingto Importance value Index (IVI). There is significant difference in density of trees, shrubs, herbs and climbers between different sample quadrats i.e. p value < 0.05. NTFPs found were used for medicine, fodder, food, veterinary, dying, handicrafts, crop management, ornamental, insecticides, construction, beverage, piscicidal, religious and miscellaneous purposes. Calamus tenuis, Curcumalonga, Piper longum, Phyllanthus emblica, Asparagus racemosus, Terminalia bellirica, Terminaliachebula, Bauhinia variegata, Tinospora sinensis and Dryopteris cochleata were ten most preferred Non Timber Forest Products from matrix preference ranking.